FRANCO-UZBEK RELATIONS ARE AT A NEW STAGE - Khamidullayev Bobur; R. F. Farmanov (Zeta Repository, 2023)
Uzbek-French relations date back to a long past, but this article is devoted to the new stage of relations between Uzbekistan and France, and the activities carried out between the two countries within the framework of the “soft power” policy are analyzed. Since 2016, mutual relations have strengthened significantly, significant work has been done in the field of culture, art, science and education.